2006
DOI: 10.1158/0008-5472.can-05-3480
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Light Chain 1 Contributes to Cell Cycle Progression by Increasing Cyclin-Dependent Kinase 2 Activity in Estrogen-Stimulated Cells

Abstract: Progression of hormone-responsive cancers is characterized by deregulation of the cell cycle and cytoskeleton signaling. In addition, development of breast and endometrial cancer is influenced by the stimulatory action of estrogen. Upregulation of dynein light chain 1 (DLC1), a component of cytoskeleton signaling, was recently found to promote tumorigenesis. The purpose of our study was to determine the role that DLC1 up-regulation plays in cell cycle progression. To achieve this goal, we used human breast duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…The central involvement of estrogen in the development and carcinogenesis of reproductive organs is well established (1,8,9,42,48,55). However, the understanding of the genomic mechanisms of estrogen action continues to evolve (14,42,56,59).…”
Section: Discussionmentioning
confidence: 99%
“…The central involvement of estrogen in the development and carcinogenesis of reproductive organs is well established (1,8,9,42,48,55). However, the understanding of the genomic mechanisms of estrogen action continues to evolve (14,42,56,59).…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione S-transferase (GST)-Ciz1 full-length and deletion constructs were generated as described earlier (11). To generate an expression vector containing Myc-tagged Ciz1 (Myc-Ciz1) or a Ciz1 expression vector with T7 tag (T7-Ciz1), Ciz1 cDNA was amplified by PCR and cloned into pCMV-Myc vector (Clontech, Palo Alto, CA) or pcDNA3.1 vector (Invitrogen), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…An earlier study from this laboratory revealed a coactivator function of dynein light chain 1 (DLC1) in targeting the ER to the chromatin of estrogen-inducible genes in breast cancer cells (10). More recently, we showed that DLC1 interacts with a novel protein, Cip-interacting zinc finger protein 1 (Ciz1), and participates in the regulation of cell cycle by increasing cdk2 kinase activity and inducing the G1-S transition (11,12). Despite the emerging significance of Ciz1 in the biology of breast cancer cells, how endogenous Ciz1 is regulated in hormone-responsive cancer cells is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CIZ1-F protein therefore lacks previously characterized functional domains, including the MH3-domain which anchors CIZ1 to the NM [8], and cyclin-binding motifs through which CIZ1 interacts with cyclin A, and which are essential for its DNA replication activity (Figure 1(b)) [6,7]. Other characterized sites of interaction with CDK2, p21 cip1 and YAP are also excluded [1517], while interaction with CDC6 [18], ERα [12], and dynein light chain [15] might be retained. The interaction sites of the CIZ1 binding factors PDRG1 [19], SH3BP4 [20], and TCF4 [21] are not yet characterized.…”
Section: Resultsmentioning
confidence: 99%
“…The CIZ1-F specific sequence, encoded by an alternative reading frame (ARF) of exon 12–13, is highlighted in light blue. Also shown are the location of K/RXL cyclin-binding motifs implicated in replication [7] (‘C’), LXXLL ER-interaction motifs (asterisks), and sequences reported for full-length CIZ1 to interact with CDC6 [18], cyclin-dependent kinase 2 (CDK2) [15], cyclins A and E [7], dynein light chain (DYNLL1) [15], estrogen-receptor (ER) [12], enhancer of rudimentary homolog (ERH) [42], p21 [16], and YAP [17]. Note that several of these interactions were discovered in mouse CIZ1, and that the reported interaction between ER and CIZ1 is not via a domain that includes LXXLL [12].…”
Section: Introductionmentioning
confidence: 99%